Pengaruh Kepemimpinan Transformasional dan Fasilitas Kerja Terhadap Kinerja Karyawan PT. Shafwa Almahyra Utama - Muyasaroh; Basuki Rahmat; Anggi Indriyanti (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2024)
How does transformational leadership influence employee performance at PT. Main Shafwa Almahyra? 2) How do work facilities influence employee performance at PT. Main Shafwa Almahyra? 3) How does transformational leadership and work facilities influence employee performance at PT. Main Shafwa Almahyra?. This aims to determine the effect of transformational leadership and work facilities on employee performance. This research uses quantitative data by distributing questionnaires to respondents, namely PT employees. Shafwa Almahyra Utama with a research population of 40 samples using saturated sampling techniques. The reliability testing technique uses the Cronbach Alpha technique with hypothesis testing using Person Product Moment correlation at a significance level of a = 5%. Based on data processing from SPSS version 25, the results of the coefficient analysis show that the r2 value is 0.750 and is stated in the strong category. The coefficient of determination formula KD = r2 x 100% so that the coefficient of determination KD = 0.7502 X 100% = 56.2%. So it can be concluded that variables X1 (Transformational Leadership) and X2 (Work Facilities) and Y (Employee Performance) have a relationship of 56.2 or rounded to 56%.